Trematode genetic patterns at host individual and population scales provide insights about infection mechanisms - Simão Correia; Sergio Fernández-Boo; Luísa Magalhães; Xavier de Montaudouin; Guillemine Daffe; Robert Poulin; Manuel Vera (Parasitology, 2023)
Multiple parasites can infect a single host, creating a dynamic environment where each parasite must compete over host resources. Such interactions can cause greater harm to the host than single infections and can also have negative consequences for the parasites themselves. In their first intermediate hosts, trematodes multiply asexually and can eventually reach up to 20% of the host's biomass. In most species, it is unclear whether this biomass results from a single infection or co-infection by 2 or more infective stages (miracidia), the latter being more likely a priori in areas where prevalence of infection is high. Using as model system the trematode Bucephalus minimus and its first intermediate host cockles, we examined the genetic diversity of the cytochrome c oxidase subunit I region in B. minimus from 3 distinct geographical areas and performed a phylogeographic study of B. minimus populations along the Northeast Atlantic coast. Within localities, the high genetic variability found across trematodes infecting different individual cockles, compared to the absence of variability within the same host, suggests that infections could be generally originating from a single miracidium. On a large spatial scale, we uncovered significant population structure of B. minimus, specifically between the north and south of Bay of Biscay. Although other explanations are possible, we suggest this pattern may be driven by the population structure of the final host.